2017
DOI: 10.1111/exd.13378
|View full text |Cite
|
Sign up to set email alerts
|

Autoantigens ADAMTSL5 and LL37 are significantly upregulated in active Psoriasis and localized with keratinocytes, dendritic cells and other leukocytes

Abstract: Psoriasis is a common immune-mediated disease that affects 2%-4% of individuals in North America and Europe. In the past decade, advances in research have led to an improved understanding of immune pathways involved in the pathogenesis of psoriasis and has spurred the development of targeted therapeutics. Recently, three psoriasis autoantigens have been described: cathelicidin (LL37), a disintegrin and metalloprotease domain containing thrombospondin type 1 motif-like 5 (ADAMTSL5), and lipid antigens generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 35 publications
(62 reference statements)
0
80
0
5
Order By: Relevance
“…LL37 and ADAMTSL5 are both potential antigens found at significantly higher concentrations in lesional skin, but they are also expressed by immune cells that are classically associated with psoriasis, namely, dendritic cells and macrophages [83]. These autoantigens also appear to be under the influence of well-established psoriatic treatment, with the concentration of ADAMTSL5 and LL37 downregulated by etanercept, ixekizumab, and brodalumab [83]. …”
Section: Resultsmentioning
confidence: 99%
“…LL37 and ADAMTSL5 are both potential antigens found at significantly higher concentrations in lesional skin, but they are also expressed by immune cells that are classically associated with psoriasis, namely, dendritic cells and macrophages [83]. These autoantigens also appear to be under the influence of well-established psoriatic treatment, with the concentration of ADAMTSL5 and LL37 downregulated by etanercept, ixekizumab, and brodalumab [83]. …”
Section: Resultsmentioning
confidence: 99%
“…34 Importantly, recent results from our laboratory suggest that the possibility of ADAMTSL5 antigen presentation and the subsequent activation of IL-17-producing T-cells in psoriatic skin may involve other immune cell populations, such as keratinocytes and dendritic cells. 37, 38 …”
Section: Psoriasis As a T-cell Mediated Autoimmune Conditionmentioning
confidence: 99%
“…Unfortunately, little is known about the exact immune events leading to the loss of immune tolerance in individuals susceptible to psoriasis. It is essential that future studies further explore these molecular mechanisms and carefully characterize the expression profiles of potential autoantigens in all cell types found in the skin and blood of psoriasis patients, 38 as well as their relationship to major psoriasis susceptibility loci.…”
Section: Psoriasis As a T-cell Mediated Autoimmune Conditionmentioning
confidence: 99%
“…It was recently shown that CD8+ T cells respond to peptides derived from the ADAMTSL5 protein in a HLA-Cw*0602 restricted fashion, resulting in release of IL-17A and IFN-γ[17]. All three of these putative autoantigens in psoriasis are strongly induced in psoriatic skin[18,19], with LL-37 and ADAMTSL5 having fairly widespread expression patterns[19], but keratin 17 expression is limited to the psoriatic epidermis[18]. …”
Section: Genetics Adaptive Immune System and Evidence For Autoimmunimentioning
confidence: 99%